2013
DOI: 10.3892/ijo.2013.1769
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide induces cell death in human TRAIL-resistant melanoma through intracellular superoxide generation

Abstract: Intracellular reactive oxygen species (ROS) such as hydrogen peroxide (H(2)O2()) are thought to mediate apoptosis induced by death receptor ligands, including tumor necrosis factor-related apoptosis-inducing ligand (TRAIL). However, the role of H(2)O(2) is controversial, since some evidence suggests that H(2)O(2) acts as an anti-apoptotic factor. Here, we show that exogenously applied H(2)O(2) (30-100 µM) induces cell death in TRAIL-resistant human melanoma cells via intracellular superoxide (O(2)-) generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 37 publications
1
55
0
Order By: Relevance
“…For example, the incubation of either bladder cancer cells or melanoma cells with low concentrations of hydrogen peroxide reverses TRAIL resistance [45, 46]. It has also been shown that quercetin, a flavonol that depletes intracellular GSH and induces ROS, can sensitize TRAIL-resistant hepatoma cells to TRAIL-induced apoptosis by multiple mechanisms [4749].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the incubation of either bladder cancer cells or melanoma cells with low concentrations of hydrogen peroxide reverses TRAIL resistance [45, 46]. It has also been shown that quercetin, a flavonol that depletes intracellular GSH and induces ROS, can sensitize TRAIL-resistant hepatoma cells to TRAIL-induced apoptosis by multiple mechanisms [4749].…”
Section: Discussionmentioning
confidence: 99%
“…Activated IRE 1 splices the mRNA for X-box-binding protein-1 (XBP-1) to allow translation of the mature spliced form of XBP-1 protein, which acts as a transcription factor and mediates the transcriptional upregulation of numerous genes involved in ER function as well as TRAIL-R2 (25). In support of the role of ERS in TRAIL-induced apoptosis, TRAIL induces the splicing of XBP-1, and membrane-depolarizing agents including high K + , U37883A (19, 21), DATS (22), H 2 O 2 (23), and mitochondrial inhibitors such as antimycin A and FCCP (20) all commonly potentiate this effect, although none of these agents except H 2 O 2 alone can induce the splicing. Only glibenclamide cannot potentiate TRAIL-induced XBP-1 activation, although it upregulates GRP78 expression in accordance with its minimal effect on TRAIL-induced cell death during the initial 24 h (19).…”
Section: Role Of the Endoplasmic Reticulum Death Pathway In The Effecmentioning
confidence: 98%
“…These include diallyltrisulfide (DATS), a major garlic organosulfur compound (22), the cell-permeable oxidant H 2 O 2 (23), and mitochondrial metabolic inhibitors such as rotenone, antimycin A, and FCCP (20). Moreover, when employed at higher concentrations and longer exposures, all of these chemicals kill malignant cells while sparing normal cells.…”
Section: Role Of the Mitochondrial Death Pathway In The Effects Of Dementioning
confidence: 99%
See 2 more Smart Citations